Cost of managing an episode of relapse in multiple sclerosis in the United States - Ward Alexandra J; O'Brien Judith A; Patrick Amanda R; Caro Jaime (BMC, 2003)
Abstract Background The purpose of this study was to determine the direct medical US cost of managing multiple sclerosis relapses. Methods Direct data analysis and cost modeling were employed to derive typical resource use profiles and costs in 2002 US dollars, from the perspective of a third-party payer responsible for comprehensive health-care. The location and scope of health care services provided over a 90-day period were used to define three levels of relapse management. Hospitalization and resulting subsequent care was defined as high intensity management. A medium level of intervention was defined as either use of the emergency room, an observational unit, or administration of acute treatments, such as intravenous methylprednisolone in an outpatient or home setting. The lowest intensity of care comprised physician office visits and symptom-related medications. Data were obtained from many sources including all payer inpatient, ambulatory and emergency room databases from several states, fee schedules, government reports, and literature. All charges were adjusted using cost-to-charge ratios. Results Average cost per person for high management level was $12,870, based on analysis of 4,634 hospital cases (mean age 48 years, 73% female). Hospital care comprised 71% of that cost. At discharge, 36% required inpatient sub-acute care, rehabilitation or home care. The typical cost per moderate episode was $1,847 and mild episode $243. Conclusions Management strategies leading to a reduction in the frequency and severity of a relapse, less reliance on inpatient care, or increased access to steroid infusions in the home, would have a substantial impact on the economic consequences of managing relapses.